COVID-19 a paradigm shift in national security: an overview of Malaysian securitization and response / Nur Ain Yaacob ... [et al.] - Yaacob, Nur Ain; Yusof, Muhammad Izmer; Mat Nurudin, Suzei; Mohd Zain, Zarina; Akmal Mustapa, Nuramira (2022)
The covid-19 virus swept the world by surprise in late 2019, and in 2020, it changed the world as we know it today. The pandemic is not just changing the health aspect of the world but also sending a clear signal on the aspect of security. For once the headline of most major news in the world was not war or a terrorist attack but an increasing number of the population that succumbs to the disease. This article will view the shifting paradigm of nation security in securitizing the pandemic to formulate a response. The tenet of Buzan's securitization theory will be used to analyze the reaction of the Malaysian government in handling the issues that clearly impact the status quo of Malaysia's social, politic and economy. The MCO or Movement Control Order implemented by the Malaysian government in Mac 2020 followed by the declaration of Emergency and the suspension of parliament is not without debate whether the securitization of these issues is supposed to combat the pandemic threat or as a political tool for power consolidation. Hence, this paper aims; i.to maps Covid 19 as a new threat to the National Security in Malaysia, ii. to analyse securitization on the spread of Covid-19 in Malaysia, iii. to identify the critics in term of economy and politics towards government response of Movement Control Order (MCO) in Malaysia.